2021
DOI: 10.1007/s10623-021-00881-9
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial invariants for nets of conics in $$\mathrm {PG}(2,q)$$

Abstract: The problem of classifying linear systems of conics in projective planes dates back at least to Jordan, who classified pencils (one-dimensional systems) of conics over $${\mathbb {C}}$$ C and $$\mathbb {R}$$ R in 1906–1907. The analogous problem for finite fields $$\mathbb {F}_q$$ F q with q odd was solved by Dickson in 1908. In 1914, Wilson attempted to classify ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Alternatively, V(F q ) is the set of points (u 00 , u 01 , u 02 , u 11 , u 12 , u 22 ) ∈ PG(5, q) for which the rank of the symmetric matrix defined by [u ij ] is 1. We use the same notation as in [19,20], where a point P = (y 0 , y 1 , y 2 , y 3 , y 4 , y 5 ) of PG(5, q) is represented by a symmetric 3 × 3 matrix…”
Section: Preliminariesmentioning
confidence: 99%
See 3 more Smart Citations
“…Alternatively, V(F q ) is the set of points (u 00 , u 01 , u 02 , u 11 , u 12 , u 22 ) ∈ PG(5, q) for which the rank of the symmetric matrix defined by [u ij ] is 1. We use the same notation as in [19,20], where a point P = (y 0 , y 1 , y 2 , y 3 , y 4 , y 5 ) of PG(5, q) is represented by a symmetric 3 × 3 matrix…”
Section: Preliminariesmentioning
confidence: 99%
“…Clearly, rank-distributions are K-invariants. The next definition introduces stronger K-invariants, first introduced in [20] and more formally in [1], which play a fundamental role in classifying subspaces of PG(5, q). Definition 2.1.…”
Section: Points Lines and Hyperplanes Of Pg(5 Q)mentioning
confidence: 99%
See 2 more Smart Citations
“…Powerful combinatorial invariants (called orbit distributions, see Section 2 below) introduced in [16] and [3], were used to determine the number of the different types of conics contained in pencils of conics in PG (2, q). In [18] it was shown that, in the case of nets of rank one over finite field of odd order, these combinatorial invariants give in fact a complete invariant for the equivalence classes of these nets.…”
Section: Introductionmentioning
confidence: 99%